БЕССОЮЗНЫЕ СЛОЖНЫЕ ПРЕДЛОЖЕНИЯ ОДНОРОДНОГО СОСТАВА В АСПЕКТЕ ПРОБЛЕМЫ ТОЖДЕСТВ И РАЗЛИЧИЙ НА ПРИМЕРЕ КАРАКАЛПАКСКОГО ЯЗЫКА - Халмуратов, Т.Ж. (SCIENCE and SOCIETY, 2025)
The article is devoted to the study of homogeneous compound sentences without conjunctions (hereinafter referred to as CWS) in the Karakalpak language in terms of the problem of identities and differences.
Keywords: complex sentences without conjunctions; the karakalpak language; structural and semantic types of sentences; the concept of identities and differences